Cognitive Decline in Multiple Sclerosis Is Related to the Progression of Retinal Atrophy and Presence of Oligoclonal Bands: A 5-Year Follow-Up Study - Giedraitiene, Natasa; Drukteiniene, Egle; Kizlaitiene, Rasa; Cimbalas, Andrius; Asoklis, Rimvydas; Kaubrys, Gintaras (Frontiers in Neurology, 2021)
Background: The main biomarker of neurodegeneration in Multiple Sclerosis (MS) is supposed to be the brain atrophy, which is associated with cognitive impairment and retinal nerve fiber layer (RNFL) atrophy. There are no many data about the relation of inflammatory markers, like oligoclonal bands (OCBs) in cerebrospinal fluid (CSF) and cognition, RNFL atrophy and brain atrophy. The aim of the study was to assess the relationship of RNFL thickness, brain atrophy markers and intrathecal OCBs either elevated IgG index on the decline of cognition per 5 years in patients with MS. Methods: Prospective single-center cohort 5-year long follow-up study was performed in relapsing MS patients. At baseline, relapsing patients underwent brain MRI. Cognitive evaluation was performed with Brief International Cognitive Assessment for MS (BICAMS) and RNFL thickness was assessed with Optical Coherence Tomography (OCT). OCBs and IgG level were evaluated at baseline in CSF. BICAMS, OCT and MRI were re-evaluated after 5 years. Results: Significant reduction in information processing speed, visual learning, temporal-RNFL thickness, Huckman index and third ventricle mean diameters was found in 49 relapsing MS patients over the observational period (p<0.05). 63.3 % of patients had positive OCBs and 59.2 % of patients had elevated IgG index in CSF. The atrophy of temporal segment and papillomacular bundle and OCBs had significant relationship with decline of information processing speed in MS patients (p<0.05), while brain atrophy markers did not reach significance in General Linear Models. Conclusions: RNFL atrophy and OCBs were related to cognitive decline in MS patients in 5-year follow-up study.